Pengaruh Jamu Cekok Terhadap Kenaikan Berat Badan Dan Jumlah Makanan Yang Dikonsumsi Mencit - Sih Rini Handajani; KH Endah Widhiastuti (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract Background: Javanese people, especially those living in the city of Solo, try to overcome the difficulty of eating children by providing special herbal medicine for children which is better known as jamu cekok. It’s believed to have efficacy as a child's appetite stimulant, as a herb that can kill irritating worms in the body of a child. This study aimed to determine the effect of herbal medicine on weight gain and the amount of food consumed by mice. Method: This research design usedpre clinicaltria in mice. The sample consisted of 60 mice divided into 3 groups, namely 20 control groups, 20 treatment groups I (given 0.25 ml slices) and Treatment Group II (given 0.5 ml of stress). Result: The time for conducting research January 2016 s.d. June 2016 at the GadjahMada University Pharmacy Laboratory Yogjakarta. The results of the analysis of herbal medicine had an effect on the weight gain with the results in the intervention group 1, the consumption of herbal medicine decreased the weight of rats by 24.3%. and in the intervention group 2 decreased the mouse rats by 0.1%. Choking affects the amount of food left over. Conclusion: The results showed that the mice given 0.25 ml less rest (amounting to 0.570 and this decrease occurred very significantly indicated by the p value <0.000) compared to those given 0.50 ml and control group.